What's Real Is Immaterial: What Are We Doing With New Materialism? - Nicholls, D (University of Ottawa, 2020)
New materialism is emerging as one of the most significant developments in healthcare research in recent years, offering radical new ways to rethink our critical relationship with forms, matter, objects and things. As with any new paradigm, it can take some time for the limitations of the approach to become clear. In this article I examine some of these limitations, focusing particularly on new materialist definitions of objects and the ontology of affect. Drawing on the recent work of Graham Harman and Timothy Morton, I argue that new materialism fails the ‘flat ontology test’, and reinforces the kinds of idealism that it purports to critique. Object Oriented Ontology, on the other hand, may allow us to shape a radical new ethics of objects, using that to transform our abusive relationship with the ecosystem, disturb traditional enlightenment binaries and hierarchies, and to put aside human hubris.
Keywords: Object oriented ontology; New materialism